Leukemoid Reaction in Infant Pertussis: Is There a Place for Hydroxyurea? A Case Report - Maitre, Guillaume; Schaffner, Damien; Natterer, Julia; Longchamp, David; Ferry, Thomas; Diezi, Manuel; Di Bernardo, Stefano; Perez, Marie-Hélène; Amiet, Vivianne (Frontiers in Pediatrics, 2018)
A 73-days old infant of 34 weeks’ gestation was hospitalized with a co-infection of respiratory syncytial virus (RSV) and Bordetella Pertussis (BP). She required invasive ventilation for nine days in the context of malignant pertussis with persistent hypoxemia and hypercapnia secondary to a leukemoid reaction. Despite an increase of white blood cell (WBC) count up to 70 G/L and ensuing pulmonary hypertension, no hemodynamic compromise occurred. Without clear indication for leukapheresis nor exchange transfusion, an off-label treatment with hydroxyurea was given for five days with gradual decrease of WBC count, without any complication and hospital discharge on day 29. To our knowledge, no effective therapy for malignant pertussis has been described in the literature and complications are frequent with leukoreduction procedures. We discuss an alternative to invasive procedures in young infants to fulfill the need to decrease rapidly leukocyte counts in a leukemoid reaction associated with Bordetella Pertussis infection. To our knowledge, hydroxyurea has never been used in malignant pertussis but is a well-known medication for oncologic and hematologic diseases such as acute myeloid leukemia or sickle cell anemia. Its effects in this setting are not well understood but the positive outcome in our patient supports the need for further studies.